The US economy today - Ashbee, Edward (Manchester ; Manchester University Press, 2010)
'The US Economy Today provides an invaluable introduction to American economic history since 1929. Its coverage includes the New Deal, the post-war boom, stagflation, Reaganomics, the Clinton and Bush years, the 2008 - 2009 economic crisis and President Obama's first hundred days. In addition, this volume considers core contemporary economic policy debates and draws conclusions about the strengths and weaknesses of the US economic model. It looks at the causes and consequences of inequality, the extent to which there is economic mobility, and the impact of globalization and foreign trade' -- p. [4] of cover.
Assessing the US economy -- The New Deal, the long boom, government and the economy -- Curtailing the role of government -- The'new economy' -- The Bush years and the credit crunch -- Foreign trade -- Inequality, mobility and the American dream -- Drawing comparisons: the US and Europe -- The Obama administration, recession and beyond.
Includes bibliographical references and index.
Keywords: United States -- Economic conditions -- 20th century; United States -- Economic conditions -- 21st century; United States -- Economic policy -- 20th century; United States -- Economic policy -- 21st century